Trace element composition and genesis mechanism of the Fuli Pb-Zn deposit in Yunnan: LA-ICP-MS and in situ S-Pb isotopic constraints - Liang, Xingyu; Li, Bo; Zhang, Xinyue; Qin, Huaikun; Li, Gao; Zhang, Chengnan (Frontiers in Earth Science, 2023)
The Fuli Pb-Zn deposit in eastern Yunnan is located in the southeast of the Sichuan-Yunnan-Guizhou (SYG) Pb-Zn metallogenic province in South China.The ore occurs in the interlayer fracture zone of the Middle Permian Yangxin Formation dolomite. The main metal-bearing minerals of this deposit are sphalerite, galena, and pyrite. Sphalerites of two colors (black and red) have been identified in the Fuli deposit. LA-ICP-MS analysis revealed that the black and red sphalerites were enriched in Cd, Cu, Ga, and Ge and depleted in Fe, Mn, and In to different degrees. In the LA-ICPMS time resolution profiles, the above-mentioned elements form a horizontal line, consistent with the changes in the contents of major elements such as Zn and S. This indicates that these elements may occur in sphalerite as a result of isomorphous substitution. However, elements such as As, Sb, Pb, and Ag fluctuate greatly in the LA-ICPMS time resolution profile, suggesting that these elements may exist as fine inclusions. Thus, the different colors of the Fuli sphalerite may be attributed to various elements such as Ni, Cu, and Ga; Ni and Cu make sphalerite purple, Cu makes sphalerite red, and Ga makes sphalerite yellow. The δ34S values ranging from 15.57‰ to 16.91‰, indicating the enrichment of 34S. These values are similar to the sulfur isotopic compositions of Permian marine sulfates, suggesting that the reduced S in the hydrothermal fluids originated mainly from evaporated sulfate via thermochemical sulfate reduction. In situ Pb isotopic composition analysis revealed 208Pb/204Pb, 207Pb/204Pb, and 206Pb/204Pb values of galena in the range of 38.5–38.651, 15.666–15.733, and 18.539–19.124, respectively. The in situ Pb isotopic ratios of most galenas plot on the field of the basement metamorphic rocks of the Kunyang Group. These in situ Pb isotopic signatures reveal that the metallogenic metals are mainly derived from basement materials. The findings of this study suggest that the Fuli Pb-Zn deposit is a Mississippi Valley-type Pb-Zn deposit controlled by the interlayer compressional structure with characteristics of carbonate-hosted, epigenetic, simple mineral symbiosis, high Pb-Zn grade, and abundant Cd, Ga, and Ge along with other dispersed elements.